Diagnostic performance of biliopancreatic endosonography in patients with intermediate risk of choledocholithiasis - Arango Molano, Lázaro Antonio (2024)
Objective: Determine the sensitivity and specificity of the ESBP for diagnosis in patients with intermediate risk of choledocholithiasis, referred to the specialized surgical Gastroenterology center of Unión de Cirujanos SAS – Oncologists of the West Zentria group – Manizales – Colombia between March 01, 2020 to January 31, 2022. Materials and methods: Retrospective cross-sectional study in patients with intermediate risk for choledocholithiasis. The diagnostic performance of ESBP was calculated and confirmed with ERCP. Negative ESBPs were followed up by telephone. Results: 752 cases with ESBP were analyzed, of which 43.2% (n=325) were positive and 56.8% (n=427) were negative. ERCP was performed in positive cases who accepted the procedure (n=317); 73.5% (n:233) were positive for choledocholithiasis, 25.8% (n=82) tumors and 0.6% (n=2) biliary roundworms. Patients with positive ESBP underwent ERCP. S= 98.3% (95% CI: 95.7-99.5) was obtained; E= 88.1% (95% CI: 79.2-94.1); PPV = 95.8% (95% CI: 92.4-98.0); NPV = 94.9% (95% CI: 87.4-98.7). The AUC of ESBP was 0.9319 (95% CI 0.8961-0.967). Conclusion: In patients with intermediate risk for choledocholithiasis, ESBP is a useful diagnostic option in the study of pancreatic pathologies, extrahepatic biliary tree, and the identification of biliary microlithiasis; Therefore, it also allows us to complement it with a therapeutic intervention such as ERCP in a single time.